PERANCANGAN APLIKASI GO LAND (WEST SUMATERA ISLAND TOUR) BERBASIS ANDROID - Iswandi, Iswandi; Rahmi, Lidya; Septiana, Trisya; Shobirin, Khairulis; Fajri, Helfikra (IAIN Batusangkar, 2019)
Talking about West Sumatra, what will surely be drawn is tourism, it is undeniable that West Sumatra is a tourist province, one of which is island tourism, including Pamusan Island, Cubadak Island, Pasumpahan Island, Pagai Island, Siberut and others. Because it needs the support of supporting applications such as inter-island transportation ordering, it needs the support of technology, one of which is inter-island transportation and also ordering food that can be delivered directly to the address. In order to help make it easier for tourists to visit the island in West Sumatra, an application called the Go Land Application was designed. The Go Land application is an application designed using the Agile system development method with the Android Studio programming language and the UML (Unified Modeling Language) system design tool. This application has several services including: Go_Land, Land_Car, Land_Food, Land_Med, Land_Rent, Land_Auto, in this application Travelers can use facilities on the island including water games, snorkeling, seafood and can be used for formal or informal events. With this application, tourists are expected to be easier, faster and safer to enjoy island tourism in West Sumatra.